Peningkatan Literasi Energi Terbarukan melalui Edukasi Panel Surya pada Siswa SMP Negeri 8 Probolinggo - Rizqa Ruviana; Luluk Edahwati; Musyaroh Musyaroh; Tria Puspa Sari; Fatkhurrohman Fatkhurrohman; M Danny Pratama Lamura; Anisah Nurul Izzah (Publikasi Pendidikan, 2026)
Low renewable energy literacy among students remains a challenge in supporting energy transition and sustainable development. This community service program aimed to improve renewable energy literacy through solar panel education and training for students at SMP Negeri 8 Probolinggo. A quantitative descriptive approach with a pretest posttest design was employed. The program involved 30 ninth grade students who participated in interactive workshops on renewable energy concepts, counseling on the role of green energy in reducing carbon emissions, and hands-on practice in basic solar panel installation and maintenance. Program outcomes were evaluated using a five-point Likert-scale questionnaire consisting of 20 statements grouped into seven assessment parameters. The results showed consistent improvements across all parameters, with percentage increases ranging from 10.7% to 39.3%. The highest improvement was observed in the maintenance and evaluation of solar panels, while the lowest increase occurred in students’ attitudes toward supporting renewable energy. These findings indicate that practice-based educational interventions are effective in enhancing students’ knowledge, basic technical skills, and environmental awareness. This program contributes to the achievement of Sustainable Development Goals, particularly SDG 4 (Quality Education), SDG 7 (Affordable and Clean Energy), and SDG 13 (Climate Action).